Nadezhda A. Puchkovskaia (110th Birth Anniversary) (Ukrainian Journal of Ophthalmology, 2026)
Nadezhda A. Puchkovskaia, an academician of the National Academy of Science and National Academy of Medical Science of Ukraine, Academy of Medical Science of RF, International Academy of Ophthalmology, Honorable member of Ophthalmology Societies and National Medical Academies of many countries, Honored Master of Sciences and Engineering, Professor, Doctor of Medical Science, a prominent scientist, ophthalmologist, and health care organizer, a disciple of V.P. Filatov and Director of the Filatov Institute for many years, was born on the 25th of May, 1908.